Strengthening conservation and utilization of ground-nut (Arachis hypogaea L.) genetic resources in West Africa - Ntare, B.R.=700 1 Waliyar, F.; Mayeux, A.H.
(En, Fr, Es)
Ilus., 15 ref.
Keywords: ARACHIS HYPOGAEA; FITOMEJORAMIENTO; CONSERVACION DEL GERMOPLASMA; RECURSOS GENETICOS; AFRICA OCCIDENTAL